Investing in Youth: Lithuania - Organisation for Economic Co-operation and Development; Organisation for Economic Co-operation and Development (Investing in Youth, ISSN 24126357, 2016)
The present report on Lithuania is the fourth of a new series on "Investing in Youth" which builds on the expertise of the OECD on youth employment, social support and skills. This series covers both OECD countries and countries in the process of accession to the OECD, as well as some emerging economies. The report provides a detailed diagnosis of the youth labour market and VET system in Lithuania from an international comparative perspective, and offers tailored recommendations to help improve school-to-work transitions. It also provides an opportunity for Lithuania to learn from the innovative measures that other countries have taken to strengthen the skills of youth and their employment outcomes, notably through the implementation of a Youth Guarantee.
Keywords: Youth : Employment; Youth : Employment : Lithuania; Lithuania